Information hiding in multimedia files : a literature review - Ali Ja’far, Abdullah Mohammed Abdo; Deris, Safaai (2006)
There are two basic idea to keep something as a secret, the object could be changed by rules to a form could not be recognized the original object just for people who know these rules and every thing about it such that thy can obtain the original object, his is called "Cryptography" which is a Greek term and mean "Secret Writing". Or an object can be hidden at a secret place; one can hope that nobody will find this object except people who are familiar with the secret sender the methodology concerned with this kind of information security is called "Steganography". In this paper we speak about literature review of steganography